Infection efficiency model for assessment of temperature rise impact on leaf blast infection in rice under climate change scenario - SHALINI SAXENA, P. NAGAMANI and P. SINHA, K. VISWANATH*, TARU SHARMA (Indian Phytopathology, 2016)
Under climate change scenario, effect of temperature rise on leaf blast (Magnaporthe oryzae) under climate change scenario in tropical rice-agro ecosystems has become an important component of adaptation strategy. Infection efficiency for leaf blast was modeled in terms of temperature response on lesion development rate. Rate of lesion development or infection efficiency, as reciprocal of median time (h-1) for 50 % of lesion development, characteristically increased with increase in temperature up to 27.5°C and then declined to towards zero at about 34.1°C. Inflection point at 20.9°C, a local maximum at 27.5°C along with lower and upper temperature limits facilitated to account temperature rise impact on blast infection for every small increase (even at 0.1°C) in temperature. Temperature dependent infection efficiency model for leaf blasmay be used for the essenssment of temperature impact.